PERANCANGAN KAWASAN HOMESTAY DI HUTA TINGGI KABUPATEN SAMOSIR BERBASIS KEARIFAN LOKAL BATAK TOBA - Simbolon, Asido Martodi; Novalinda, Novalinda (Jurnal Teknik dan Teknologi Indonesia, 2024)
Indonesia is a country renowned for its rich natural resources and cultural heritage. The tourism sector, particularly in North Sumatra, includes the Batak Toba culture as one of its highlights. One aspect of Batak Toba culture reflects the potential for cultural tourism in Huta Tinggi, Samosir Regency. To develop and enhance the potential of the tourism sector in Huta Tinggi, and as an effort to preserve cultural heritage, it is necessary to establish a homestay building. A homestay plays an important role in the development of the Huta Tinggi area. The design of the homestay area adopts a local wisdom-based approach using the modern (Neo-Vernacular) Batak Toba architectural style. This is because Neo-Vernacular architecture represents a modern form that still retains the image or distinctive characteristics of the region, with a design that is adapted to contemporary contexts.